Assessment of Microhardness of Bulk-Fill Class II Resin Composite Restorations Performed by Preclinical Students: An In Vitro Study - Hassan, Ali Abdel-Halim Abdel-Azim; Sindi, Abdulelah Sameer; Atout, Abeer Mohamed; Morsy, Mohamed SM; Mattoo, Khurshid A.; Obulareddy, Vishnu Teja; Mathur, Ankita; Mehta, Vini (European Journal of General Dentistry, 2024)
Objectives A comparable performance between bulk-fill composites (BFCs) and progressively inserted conventional resin composite (CRC) has been observed in previous studies. However, a significant number of dental institutions in India continue to employ incremental techniques for RC restorations during preclinical studies. But as BFCs are gaining popularity, they may soon be a part of the curriculum for dental students. The aim of this study was to assess the microhardness and the polymerization efficiency of bulk-fill composites versus CRC in class II slot preparations restored by second-year dental students on ivorine mandibular first molar teeth with high-intensity (HI) and low-intensity (LI) light-curing units using the standard mesial slot preparation technique.Material and Methods Fifty preclinical dental students of second year of a dental college were recruited for the study on a voluntary basis. During their preclinical instructions, all participants were taught and made to practice the handling and curing techniques for two-surface RC restorations for 4 months. Each student was asked to perform four RC restorations: CRC-HI, CRC-LI, BFC-HI, and BFC LI. Assessment of microhardness was done using the Vickers microhardness (VMH) test.Statistical analysis One-way and multivariate analysis of variance and Bonferroni 's post hoc test tests were used for data analysis.Results The results showed a significant decrease in the VMH readings in the horizontal axis, progressing from the uppermost to the lowermost positions (p > 0.05). In all the examined groups, the VMH values at the deepest reading locations were found to be higher than 80% of the values observed at the occlusal surface reading locations. Statistically significant associations were seen between the RC type and the light source used in the VMH readings conducted (p > 0.05). However, no significant correlation was identified between the type of light source and the vertical VMH readings (p > 0.05).Conclusion Instructing dental students to place RC restorations using CRC or BFC materials together with both HI and LI light-curing protocols is safe and can be considered for preclinical studies.
Keywords: dental students; Vickers microhardness; preclinical studies; resin composite; bulk-fill